Peran Perawat Dengan Pemenuhan Kebutuhan Keluarga Pasien Kritis Di ICU - Imamah, Ida; Mustika, Yuli; Husain, Fida’ (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) ITS PKU Muhammadiyah Surakarta, 2023)
Introduction: The presence of critical patients being treated in intensive care can hurt on the physical and psychological condition of their families, including lack of attention to personal hygiene, insomnia, decreased appetite, anxiety, depression and post-traumatic syndrome disorder (PTSD). This negative impact can be minimized through the role of nurses by meeting the family's needs while the patient is being treated in the intensive care room. Objective: This research aims to determine the description of meeting the needs of families of critical patients by nurses in the ICU at Ario Wirawan Lung Hospital, Salatiga. Method: The design of this research is descriptive with a survey approach using a questionnaire developed from the Critical Care Family Needs Inventory (CCFNI). The sampling technique used was total sampling with a total of 30 nurses as respondents. The data analysis used is univariate and bivariate. Results: Research shows that the majority of respondents, 60% or 18 nurses, have a good role. On average, the categories for fulfilling the needs of the patient's family carried out by nurses were the same, namely the good and bad categories for 15 respondents or 50%. Bivariate analysis results p value = 0.000 (< 0.05). Conclusion: There is a relationship between the role of nurses and meeting the needs of the families of patients treated in the ICU.